Polyurethane polystyrene based smart interpenetrating network with quick shape recovery through thermal actuation. (9th February 2022) - Ahmed, Naveed; Atif, Muhammad; Ahmed, Nisar; Iftikhar, Fatima; Nauman, Saad; Niaz, Basit
Polyurethane (PU), designed with pre-polymer method involving polyol as cross-linker, has been utilized for shape memory applications. Neat PU or PU-PS (polystyrene) interpenetrating network (IPN) samples have been prepared. Functionalized multiwall carbon nanotubes (FMWCNTs) have been utilized as reinforcements. PU composites have been studied for shape recovery time and found better than neat PU. 1wt% incorporation of FMWCNTs in PU has reduced shape recovery time to 22 s for 100% shape recovery, in comparison to neat PU with 62 s of 100% shape recovery. PU-PS IPN has reduced 100% shape recovery time to 17s. Superior hydrogen bonding in neat PU has been suggested as per longer shape recovery time against thermal actuation, in comparison to PU composite and IPNs with FMWCNTs. Decreased thermal stability has been observed with FMWCNTs incorporation, indicating enhanced heat dissipation. Field emission scanning electron microscopy analyses confirmed the difference of morphologies in neat PU, PU composite, and IPNs. A distinctive filler-matrix interaction in IPNs has been observed. XRD confirmed the presence of amorphous component. Rutherford Backscattering Spectrometry and Thermal Gravimetric Analysis have been utilized for analyses. Shape recovery study has been made by a simple experimental set up prepared in lab.